The Role of Gender, Financial Literacy, and Love of Money in the Motivation and Personal Financial Management of Micro, Small, and Medium Enterprises (MSME) Actors - Mustafa, Mutmainna; Hamid, Rahmad Solling; Syamsuddin, Sofyan; Ikbal, Muhammad (Proceedings Series on Social Sciences & Humanities, 2024)
Background: Gender, financial literacy, and the love of money are pivotal factors influencing the motivation and personal financial management strategies of individuals engaged in micro, small, and medium enterprises (MSMEs). Understanding how these variables interplay can provide valuable insights into enhancing financial decision-making within this crucial economic sector. This study aims to examine the relationship of gender, financial literacy, love of money, motivation and personal financial management of MSME Actors. Method: The empirical analysis was conducted using a sample of 150 MSME actors. This study used online survey for the data collection. After passing reliability and validity tests, the data were analyzed with partial least squares structural equation modeling. Results: The research results indicate that gender has a significant positive direct influence on motivation. Financial literacy also has a significant direct positive influence on motivation. Furthermore, the love of money has a significant positive direct influence on motivation. Finally, motivation also has a significant positive influence on financial management. Conclusion: In conclusion, this study highlights the intricate relationship between gender, financial literacy, the love of money, motivation, and personal financial management among MSME actors. The findings underscore the importance of addressing gender-specific factors and promoting financial literacy to enhance motivation and improve financial decision-making within the MSME sector. Moreover, recognizing the nuanced influence of attitudes towards money can further inform strategies to empower and support individuals engaged in these enterprises, ultimately contributing to their long-term financial success.